Between the Documentary Voices and the Storytelling Methods of Four Indonesian Biographical Documentaries - Adhyanggono, G.M. (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
This article examines the correlation between the voices of documentary films and the storytelling methods of four Indonesian biographical documentaries as the objects of analysis. They are Mendengar Si Bisu Bernyanyi: Biografi Pramoedya Ananta Toer (Srikaton, 1995), Ki Hadjar Dewantara: Mata Air Kebangsaan (Anshoriy, 2017), Bapak Komik Indonesia: Biografi R.A. Kosasih (Ahdan, 2019), Melawan Lupa: Polisi Jujur itu Bernama Hoegeng (Taharani, 2020). The documentary voice suggests the perspective, argument, or position of the filmmakers expressed in their works. As to the scope of storytelling includes elements of documentary narrative style, modes and power of documentary storytelling, modes of documentary presentation, and montage editing. With these two aspects – the voices and the storytelling methods – the audience has better access to gain insights from the documentaries. The analysis is carried out by making use of the filmic close reading and note-taking method through cinematic observation and interpretation. The finding suggests that the voices of the films are ideationally and aesthetically articulated through their storytelling methods. The documentary voices and their storytelling methods play a crucial part in helping the films build their credibility in line with the evidence employed.